2019
DOI: 10.1111/dom.13919
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic bioequivalence of proposed biosimilar MYL‐1501D with US and European insulin glargine formulations in patients with type 1 diabetes mellitus

Abstract: Aims To report phase 1 bioequivalence results comparing MYL‐1501D, US reference insulin glargine (US IG), and European reference insulin glargine (EU IG). Materials and methods The double‐blind, randomized, three‐way crossover study compared the pharmacokinetic (PK) and pharmacodynamic (PD) characteristics of MYL‐1501D, US IG and EU IG. In total, 114 patients with type 1 diabetes (T1DM) received 0.4 U/kg of each study treatment under automated euglycaemic clamp conditions. Insulin metabolite M1 concentrations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
(50 reference statements)
3
13
0
1
Order By: Relevance
“…There were no significant safety findings in either treatment group. Both BAX‐HI and NOVO‐HI were generally well tolerated; the type and frequency of AEs reported were consistent with other insulin products 11,28,29 …”
Section: Discussionsupporting
confidence: 67%
“…There were no significant safety findings in either treatment group. Both BAX‐HI and NOVO‐HI were generally well tolerated; the type and frequency of AEs reported were consistent with other insulin products 11,28,29 …”
Section: Discussionsupporting
confidence: 67%
“…Findings from the present study contribute to previously published data providing evidence that MYL‐1501D is a biosimilar “follow‐on biological” to insulin glargine with efficacy and safety profiles similar to the reference product. MYL‐1501D has an amino acid sequence identical to that of reference insulin glargine, and comparative PK/PD studies demonstrated the bioequivalence of MYL‐1501D to both US and European insulin glargine in patients with T1DM . Similar results were observed in patients with T2DM; MYL‐1501D was shown to be non‐inferior to reference insulin glargine .…”
Section: Discussionmentioning
confidence: 62%
“…Currently, MYL‐1501D is being investigated as a biosimilar to insulin glargine in the European Union (EU) and as a follow‐on biological to insulin glargine in the United States for management of T1DM. A phase I pharmacokinetic/pharmacodynamic (PK/PD) study comparing MYL‐1501D with EU‐ and US‐sourced reference insulin glargine demonstrated PK/PD equivalence among the three formulations . The present paper presents the results from INSTRIDE 1, a 52‐week, open‐label, randomized, phase III study that compared efficacy and safety of MYL‐1501D and reference insulin glargine in patients with T1DM (http://clinicaltrials.gov identifier, NCT02227862).…”
Section: Introductionmentioning
confidence: 99%
“…MYL1501D insulin glargine is a long-acting human insulin analogue manufactured by recombinant DNA technology in Pichia pastoris (a yeast) [5]. It has similar physicochemical characteristics and biological properties to those of EU-and US-sourced reference insulin glargine 100 U/mL [7], with a dose of 0.4 U/kg demonstrating pharmacodynamic and pharmacokinetic bioequivalence to 0.4 U/kg of EU-and US-sourced reference insulin glargine 100 U/mL in a randomized, double-blind, phase I, crossover study in 113 adults with type 1 diabetes [8] (Table 1). The three-way crossover design of this study permitted the demonstration of pharmacodynamic and pharmacokinetic bioequivalence between EU-and US-sourced reference insulin glargine 100 U/mL, establishing a three-way bridge between MYL1501D insulin glargine, EU-sourced reference insulin glargine 100 U/mL and US-sourced reference insulin glargine 100 U/mL (data from an abstract) [9].…”
Section: Pharmacological Properties Of Myl1501d Insulin Glarginementioning
confidence: 99%
“…autophosphorylation) the two insulin receptor isoforms and the insulin growth factor receptor), glucose uptake activity, cell proliferation, potency] [7] Bridging studies established an analytical bridge between EU-and US-sourced reference insulin glargine 100 U/mL [7] Pharmacodynamic similarity Bioequivalent (i.e. 90% CIs of the geometric LSM ratios were within the predefined range of 0.80-1.25) to both EU-and US-sourced reference insulin glargine 100 U/mL in terms of the primary pharmacodynamic parameters (area under the GIR-time curve from 0 to 30 h, maximum GIR) in adults with type 1 diabetes [8] GIR profiles were nearly superimposable for MYL1501D insulin glargine, EU-sourced reference insulin glargine 100 U/mL and US-sourced reference insulin glargine 100 U/mL [8] Pharmacokinetic similarity Bioequivalent (i.e. 90% CIs of the geometric LSM ratios were within the predefined range of 0.80-1.25) to both EU-and US-sourced reference insulin glargine 100 U/mL in terms of the primary pharmacokinetic parameters (AUC from 0 to 30 h, C max ) in adults with type 1 diabetes [8]…”
Section: Mechanism Of Actionmentioning
confidence: 99%